Aplicación de una auditoría financiera de la cuenta de inventaríos de una empresa dedicada a la comercialización de materia prima para la elaboración de plásticos: período 2008 - Rivera Reyes, Arturo (2010)
The auditory of financial statements is of vital importance to businesses because they allow to assess and analyze financial statements and thus can give a reasonable opinion, the objective of this thesis is the analysis of item inventories, because this account is more impact on the company engaged in the marketing of raw material for plastics processing, the analysis was made in the period 2008. To make the study of the mind we evaluated the company's internal control in order to ascertain their deficiencies. We used financial analysis tools as well as horizontal perform an ABC analysis for company products, stratified statistical design was applied to determine the size of the test sample, then followed a stock check to determine if there were material errors in Inventory account.